Anisotropic solid-state PLA foaming templated by crystal phase pre-oriented with 3D printing: cell supporting structures with directional capillary transfer function. Issue 15 (16th March 2022) - Lepcio, Petr; Svatík, Juraj; Režnáková, Ema; Zicha, Daniel; Lesser, Alan J.; Ondreáš, František
Abstract : A unique, yet simple and versatile method for preparing hierarchically aligned microporous canals using a biocompatible polymer polylactic acid (PLA) with their structure controlled at the submicron to macro scale is presented. Abstract : Bones represent a superb biomaterial that combines high mechanical stiffness with nutrition delivery to its osteocyte cells through the microscopical Haversian canals and bone canaliculi. Such a structure is hard to reproduce artificially, though. 3D printing delivers an unprecedented shape control of the created objects. Yet the resolution limit of the most common 3D printers is insufficient, lying between tens to hundreds of microns, while more precise 3D printing techniques fail in fabricating larger objects. We present a unique, yet simple and versatile method for preparing hierarchically aligned microporous canals using a biocompatible polymer polylactic acid (PLA) with their structure controlled at the submicron to macro scale. The layout was inspired by the microscopical Haversian canals and bone canaliculi of cortical bone. This procedure takes advantage of the PLA complex crystalline behavior, which was pre-oriented by 3D printing, orientedly crystallized in CO2, foamed, and cryo-shrunk. The canal formation was assessed via WAXS, FTIR spectroscopy, and DSC and complemented by the evaluation of mechanical properties, biocompatibility, and directionally selective capillary transport in the final structure. The fine dimensions of the canals unmatched by the common 3D printing techniques capable of making macroscale objects combined with the abovementioned properties represent promising potential for various applications, such as advanced cell-supporting designs with a built-in nutrition function.